Direito intertemporal em matéria de provas - Coelho, Daniel Pereira (2017)
Article 1.047 of the 2015 Civil Procedure Code, by providing transitional provisions on evidence rights, brought to the forefront a relevant and necessary debate on the intertemporal law on evidence in the civil procedure arena. For a long time now, there has been a discussion about the (ir)retroactivity (subjectivists) and immediate effect (objectivists) of law, with special attachment to the evidence rules` legal nature for the identification of the conflict resolution regime arising from the pretension of simultaneous incidence of succeeding and succeeded laws. Due to the insuperable dissent among those who have always intended to establish an universal criteria, unbreakable dogmas or fixed and invariable rules, but have always arrived, although by using different paths, to the same results, it is necessary to meditate about the substitution of abstract schemes aprioristically fixed through the adoption of principles to be used as guidelines in the evaluation process, always in accordance with the peculiarities of the concrete case. Thus, an attempt has been made to identify the adequate understanding and assortment of the transitional provision and the intertemporal law in the arena of the legal intertemporality, with a crucial view to the relation between these institutes and to the evolvement of the several doctrines about intertemporal law, investigating the existence of procedure vested rights with the aim to establish an adequate constitutional interpretation of the aforesaid transitional provisions found in the 2015 Civil Procedural Code, without forgetting the analysis of the specific conflicting situations caused by the developments implemented by the new Civil Procedure Statute